2014
DOI: 10.1177/1934578x1400901112
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Derivatives from Radix Astragali and their Anti-inflammatory Activities

Abstract: Two new (3, 4) and two known phenolic derivatives (1, 2) were isolated from Radix Astragali. The structures of 1–4 were elucidated by extensive spectroscopic analysis. The anti-inflammatory activities of the isolated compounds were evaluated in LPS-induced mouse peritoneal macrophages. All four compounds exhibited potent inhibitory effects on TNF-α production and TNF-α, COX-2, IL-1β, IL-6 and iNOS mRNA expression at 50 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Twelve articles reported that Huangqi could inhibit the generation of NO by LPS-activated macrophages [ 29 – 40 ]; eight studies were performed on Huangqi extracts, including crude extracts, active fractions, and compounds [ 31 , 34 40 ], two studies on polysaccharides [ 29 , 30 ], and another two on saponins and total flavonoids separately [ 32 , 33 ]. Seven articles separately reported that Huangqi could induce normal macrophages in a resting state to generate NO, focusing on polysaccharides and saponins, with polysaccharides (6 studies) being the most studied [ 43 – 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve articles reported that Huangqi could inhibit the generation of NO by LPS-activated macrophages [ 29 – 40 ]; eight studies were performed on Huangqi extracts, including crude extracts, active fractions, and compounds [ 31 , 34 40 ], two studies on polysaccharides [ 29 , 30 ], and another two on saponins and total flavonoids separately [ 32 , 33 ]. Seven articles separately reported that Huangqi could induce normal macrophages in a resting state to generate NO, focusing on polysaccharides and saponins, with polysaccharides (6 studies) being the most studied [ 43 – 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, saponins in Radix Astragali have attracted much attention for their unique structures and significant biological activities, including anti‐inflammatory (Ryu et al ., ; Chen et al ., ), hematopoietic functions (Zheng et al ., ), renoprotection (Meng et al ., ), anti‐hyperglycemic (Yin et al ., ; Tang et al ., ), antioxidative (Sun et al ., ), cardioprotective (Lau et al ., ; Xu et al ., ) and immunomodulatory (Wang et al ., ) effects. Astragaloside III (AST III, chemical structure shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] Ligustrazine contained in CX has a certain anticoagulant effect, which can significantly increase blood flow in coronary arteries, reduce blood viscosity and promote microcirculation [21] ; GE contains gastrodin, which has strong anti-inflammatory and antioxidant effects, and can significantly improve headache, dizziness, and spasticity, and effectively reduce the discomfort of patients [22] ; AG extract can reduce the production of inflammatory factors such as cyclooxygenase 2, IL-1β, and IL-6 in the body. [23,24] The "drug-compound-target" network shows that kaempferol, quercetin, and dauricine have the highest degree values, suggesting that they play an important role in the treatment of CS with SJTLG. Some studies have shown that kaempferol can reduce the production and mRNA expression of pro-inflammatory cytokines such as interleukin-8, thymic stromal lymphopoietin and tumor necrosis factor, and may exerts its anti-inflammatory effects through the p38MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[19,20] Ligustrazine contained in CX has a certain anticoagulant effect, which can significantly increase blood flow in coronary arteries, reduce blood viscosity and promote microcirculation [21] ; GE contains gastrodin, which has strong anti-inflammatory and antioxidant effects, and can significantly improve headache, dizziness, and spasticity, and effectively reduce the discomfort of patients [22] ; AG extract can reduce the production of inflammatory factors such as cyclooxygenase 2, IL-1β, and IL-6 in the body. [23,24]…”
Section: Discussionmentioning
confidence: 99%